Atuação do terapeuta ocupacional na unidade de terapia intensiva neonatal: um estudo da prática - Matos, Francielli (2020)
Occupational Therapy aims to compose a team from the Neonatal Intensive Care Unit (NICU) in order to contribute with strategies that favor the welcoming and interventions for the demands of the newborn and his family. In this context, intensive care, a literature indicates that the occupational therapist must be attentive to the baby's signs, clinical condition and environmental conditions, in order to favor brain development and neonatal physiological stability. The Southeast is a region with the highest concentration of NICUs, in addition to being the region where it produces the most knowledge on this subject. The general objective of this study is to characterize the practice of Occupational Therapists at the NICU in the State of São Paulo. Specifically, it is intended to verify the professional profile of occupational therapists who work in the NICU; identify how actions performed by occupational therapists within the scope of the NICU and propose an observation guide for the practice of occupational therapists working in the NICU. This study has a descriptive character, predominantly qualitative approach and data data through semistructured interviews. The interview was conducted with 8 occupational therapists from 5 cities in the state of São Paulo. It appears that the practice of these professionals is specialized in working with newborns, with a family, with a team and, even, without a physical environment of the NICU. Professional challenges related to excessive functions within the hospital, the lack of recognition on the part of the team and the difficulty in finding specific theoretical references directed to practice are also mentioned. The study allowed to know the practice of 8 professionals, occupational therapists, working in neonatal intensive care units, showing their experiences, methods and challenges. The data also reaffirm an emergency in this field for Occupational Therapy. This study, although limited by the limited number of participants, presents results that clarify and detail the practice of occupational therapists working in the NICU, who can contribute to the promotion of the profession in this field.